Radiotherapy of malignant pheochromocytoma—a case report - Yeh, Chi-Yuan (Therapeutic Radiology and Oncology, 2019)
Pheochromocytomas (PCC) are rare tumors with an estimated incidence of 0.4 to 9.5 cases per 1 million per year. About 5–26% of PCC are malignant and presents with metastasis, for which there is currently no effective therapy. The treatment of choice is for PCC is radical surgery to reduce tumor burden, to provide symptomatic relief of catecholamine excess although complete eradication of the lesions is often not feasible. A number of case reports have been published on the role of radiotherapy for the treatment of PCC. Here we present a 53-year-old male stage III malignant PCC patient who received postoperative adjuvant radiotherapy. A review of current literature is also presented.